Internship during Covid-19 pandemic: accounting undergraduates experience / Rozaiha Ab Majid … [et al.] - Ab Majid, Rozaiha; Mohd Ali, Nor Aishah; Abdullah, Salina; Mediawati, Elis; Widaningsih, Mimin (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
This paper intends to explore the challenges encountered by the Accounting undergraduates whilst undergoing their internship during Covid-19 pandemic. A set of structured questionnaires were used to elicit information on the issues and challenges that they have encountered during their internship in Covid-19 pandemic setting. A total of 367 responses were analysed. Findings indicate that the students encountered several challenges during the period of Covid19 pandemic. Working from homes has affected the normal working condition such that they feel that they are lacking in communication skills, thus less opportunity to gain better understanding on the accounting or auditing skills and knowledge. They have also learnt to be more independent in making decision while dealing with clients from home. This study only considers the interns of Accountancy undergraduate within a single accounting programme. Hence, any characteristics inherent to the respondents in this sample that differ from the overall population of accounting programme could bias the results and limits its generalization. Future research may take into consideration comparisons of internship across institutions and fraternity. Internship has become part of requirements to graduate in Accounting fraternity. To date, most studies on internship challenges during pandemic focus only to those from Science discipline. Therefore, this study can be a preliminary study to provide important information for decision makers involved in successful implementation of internship for a social science course in terms of working setting during pandemic. In addition, it may also assist policymakers on their preparedness for future possible pandemic situation.